Decomposição anaeróbia de Hedychium coronarium J. Koenig e Urochloa subquadripara (Trin.) R.D. Webster em meios com Zn e Pb - Moitas, Marcel Loyo (Universidade Federal de São Carlos, 2014)
The aim of this study was to evaluate the role of Zn and Pb in the anaerobic decomposition of aquatic macrophytes. Considering this purpose, bioassays with Hedychium coronarium coronarium and Urochloa subquadripara from Fazzari and Espraiado lagoons (São Carlos, SP, Brazil) were performed in laboratory. The kinetics of macrophytes detritus decompositions was conducted during 100 days. The pH, electrical conductivity and ratio E4/E6 was measured along this period. This procedure was carried under 6 experimental conditions: C1 (control), C2 (control plus KNO3), Zn95 (95.3 mg.L-1), Zn2 (2.0 mg.L-1), Pb6 (6.0 mg.L-1) and Pb06 (0.06 mg.L-1). Each of these conditions was also tested under two temperatures (15°C and 25°C) with the aim of evaluate the seasonality effect on the process. The organic and inorganic carbon data was fit to a kinetics model. Zinc and lead concentrations decreased the rate of particulate organic carbon loss of H. coronarium, which was observed by lower k4 and kT values. The highest zinc concentration performed the most aggressive effect causing very little loss of particulate organic carbon. Also mineralization of H. coronarium did not occur in any of the experimental conditions including control (C1), which can be associated with antimicrobial effect of some natural products in the plant. The COP loss and the COD increase were possibly related to fermentative microorganisms. The organic carbon breakdown was the only process represented by the mathematical model adopted. Zinc and lead concentrations decreased or increased U. subquadripara refractory organic carbon loss (k4) depending on condition. These differences are probably related to interactions of metals with the macrophyte detritus and humic substances produced along the process, changing thus the bioavailability of metals for heterotrophic microorganisms. Also, the highest zinc concentration condition (Zn95) had a negative effect on mineralization of U. subquadripara, showing that metal can affect mineralization and organic carbon decay independently. Overall, the kinetic model used represented the decomposition dynamics of U. subquadripara. The temperature showed a positive correlation with both plants detritus breakdown. We conclude the Zn and Pb can play a driving force role on the anaerobic decomposition of macrophytes, reducing or inhibiting heterotrophic activity. Also, we conclude that Zn and Pb had different effects for H. coronarium and U. subquadripara. Zinc showed independent effect on mineralization and POC breakdown processes. Finally, metals adsorption on detritus and humic substances are processes that determine its influence on decomposition.
Keywords: Metais; Macrófitas aquáticas; Zinco; Chumbo; Mineralização; Metals; Mathematical models; Mineralization; Aquatic macrophytes; CIENCIAS BIOLOGICAS::ECOLOGIA